Increased prevalence and risk of atherosclerotic cardiovascular disease in individuals with Type 1 diabetes and metabolic dysfunction-associated steatotic liver disease - Jonathan Mertens; Jonas Weyler; Eveline Dirinck; Luisa Vonghia; Wilhelmus J. Kwanten; Luc F. Van Gaal; Benedicte Y. De Winter; Sven Francque; Christophe De Block (Cardiovascular Diabetology)
Abstract Objective This study aimed to investigate the correlation between metabolic dysfunction-associated steatotic liver disease (MASLD) and atherosclerotic cardiovascular disease (ASCVD) in individuals with type 1 diabetes (T1D). Methods Adults with T1D (n = 659) were consecutively screened for liver steatosis via abdominal ultrasound. The presence of macrovascular disease (including coronary artery disease [CAD], peripheral artery disease [PAD], or ischaemic stroke [CVA, cerebrovascular accident]) was identified via electronic medical records. The 5- and 10-year risks of fatal/nonfatal ASCVD were assessed via the Steno Type 1 Risk Engine. Insulin resistance was assessed via the estimated glucose disposal rate (eGDR). Results The MASLD prevalence was 16.8%. The prevalence of composite ASCVD (18.9 vs. 6.8%, p < 0.001), CAD (9.9 vs. 4.7%, p = 0.031), PAD (9.0 vs. 2.2%, p < 0.001) and CVA (6.3 vs. 1.1%, p = 0.002) was greater in people with MASLD. The 5-year (7.8 [2.1–14.4] vs. 4.8 [1.6–12.0]%, p = 0.034) and 10-year (15.0 [4.1–26.8] vs. 9.4 [3.1–22.5]%, p = 0.035) risks of ASCVD were greater in those with MASLD. MASLD was associated with prevalent ASCVD (adjusted OR 4.26, 95% CI 1.79–10.11, p < 0.001), independent of age, sex, diabetes duration, smoking, statin use, LDL-cholesterol, the glomerular filtration rate, albuminuria, and metabolic syndrome. Conclusion MASLD is associated with both an increased prevalence of ASCVD and an increased calculated risk of fatal/nonfatal ASCVD in people with T1D.